A concise enantioselective synthesis of pyrrolidine sedum alkaloids (R)-(R)-(+), (S)-(S)-(−)-pyrrolsedamine and (S)-(R)-(+)-pyrrolallosedamine by using proline catalysed α-amination reaction. Issue 36 (7th September 2017) - Bhosale, Viraj A.; Markad, Sachin B.; Waghmode, Suresh B.
Abstract: A general approach for the synthesis of pyrolidine member of sedum alkaloids has been developed by employing proline catalysed sequential α-amination and Horner–Wadsworth–Emmons (HWE) olefination of an aldehyde as the key steps. This method can be extended for the synthesis of various bioactive natural products containing pyrolidine skeleton. Graphical abstract: